Human resource management : Functions, applications, and skill development - Lussier, Robert N.; Hendon, John R. (Los Angeles SAGE, 2019)
The book includes all of the latest SHRM 2016 Curriculum Guidebook listings, covering every SHRM guide item, including both the SHRM Certified Professional (SHRM-CP) and the Human Resource Certification Institute Professional in Human Resources (PHR) certification exam-a total of more than 210 individual content requirements from the SHRM curriculum guide. A three-pronged approach-functions, applications, skill development-helps students master the concepts, apply them, and build the skills needed in the workplace.
Keywords: Quản trị kinh doanh